The Virucidal Effect of the Chlorination of Water at the Initial Phase of Disinfection May Be Underestimated If Contact Time Calculations Are Used - Fredy Saguti; Inger Kjellberg; Marianela Patzi Churqui; Hao Wang; Timur Tunovic; Jakob Ottoson; Olof Bergstedt; Helene Norder; Kristina Nyström (Pathogens, 2023)
For the microbiological safety of drinking water, disinfection methods are used to remove or inactivate microorganisms. Chlorine and chlorine dioxide are often used as disinfectants in drinking water treatment plants (DWTPs). We investigated the effectiveness of these chemicals in inactivate echovirus 30 (E30), simian 11 rotavirus (RV SA11), and human adenovirus type 2 (HAdV2) in purified water from a DWTP. Within two minutes of contact, chlorine dioxide inactivated E30 by 4-log10, RV SA11 by 3-log10, and HAdV2 could not be detected, while chlorine reduced E30 by 3-log10, RV SA11 by 2–3log10, and HAdV2 by 3–4log10. However, viral genomes could be detected for up to 2 h using qPCR. The CT method, based on a combination of disinfectant concentration and contact time, during such a short initial phase, is problematic. The high concentrations of disinfectant needed to neutralize organic matter may have a strong immediate effect on virus viability. This may lead to the underestimation of disinfection and overdosing of disinfectants in water with organic contamination. These results are useful for the selection of disinfection systems for reuse of treated wastewater and in the risk assessment of water treatment processes using chlorine and chlorine dioxide.